Applying a novel visual-to-touch sensory substitution for studying tactile reference frames - Or Yizhar (Nature Portfolio, 2021)
Abstract Perceiving the spatial location and physical dimensions of touched objects is crucial for goal-directed actions. To achieve this, our brain transforms skin-based coordinates into a reference frame by integrating visual and posture information. In the current study, we examine the role of posture in mapping tactile sensations to a visual image. We developed a new visual-to-touch sensory substitution device that transforms images into a sequence of vibrations on the arm. 52 blindfolded participants performed spatial recognition tasks in three different arm postures and had to switch postures between trial blocks. As participants were not told which side of the device is down and which is up, they could choose how to map its vertical axis in their responses. Contrary to previous findings, we show that new proprioceptive inputs can be overridden in mapping tactile sensations. We discuss the results within the context of the spatial task and the various sensory contributions to the process.